An uncommon vascular cause of spontaneous hydropneumothorax - Balakrishnan, Dhayal; Mohamad Saini, Suraini; Mohd Nor, Hazman; Jamil, Hariati; Mahmud, Rozi; Abdul Rahim, Ezamin (Universiti Putra Malaysia Press, 2018)
This paper highlights a potentially life threatening and unsuspected case of multiple small pseudoaneurysms from the thyrocervical and costocervical branch of the left subclavian artery that was spontaneously ruptured. The cause was not suspected prior to thoracic CT angiography (CTA) because the initial pre-emptive diagnosis was only trivial spontaneous hydropneumothorax which became serious after a chest tube was inserted.